2017
DOI: 10.3233/cbm-170568
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA31-NDRG3 regulation axes are essential for hepatocellular carcinoma survival and drug resistance

Abstract: We conclude that miR-31 is a crucial regulator in hepatocellular carcinoma, miR-31 and its target gene NDRG3 may be potential therapeutic targets for HCC treatment in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…38,39 Present works have confirmed that miR-31 is downregulated in liver cancer and involved in liver cancer cell apoptosis, migration impairment, and proliferation delay. 10,40 But the underlying mechanisms remain unclear. The present study fills this gap and confirmed that miR-31 promotes HepG2 cells mitochondria-related apoptosis and inhibits proliferation and metastasis by activating the ROCK1/F-actin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Present works have confirmed that miR-31 is downregulated in liver cancer and involved in liver cancer cell apoptosis, migration impairment, and proliferation delay. 10,40 But the underlying mechanisms remain unclear. The present study fills this gap and confirmed that miR-31 promotes HepG2 cells mitochondria-related apoptosis and inhibits proliferation and metastasis by activating the ROCK1/F-actin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the majority of patients lose the chance to undergo radical surgery, which seriously threatens patient health and quality of life (21). The prognosis of patients is poor (22). The traits of complex diseases are affected by the interaction of multiple genes.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor suppressor miR-122 has been found to promote adriamycin sensitivity in HCC cells through inhibiting cell cycle, anti-apoptotic effector factors and ABC transporters [82][83][84]. Similarly, miR-31 has been found to increase the sensitivity of HCC cells to adriamycin via silencing the expression of NDRG3 [85]. In addition, down-regulated expression of tumor suppressor miRNAs, such as miR-223, miR-133a, miR-326, miR-101, miR-199a-3p, miR-215, miR-145 and miR-503, are significantly correlated with adriamycin resistance of HCC through inhibiting expression of the MDR-related genes.…”
Section: Mirnas and Resistance To Adriamycinmentioning
confidence: 99%